2010
DOI: 10.3174/ajnr.a2262
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Pachymeningeal Enhancement and Subdural and Subarachnoid Space Opacification on Delayed Postcontrast Fluid-Attenuated Inversion Recovery Imaging in Spontaneous Intracranial Hypotension: Visualizing the Monro-Kellie Hypothesis: Fig 1.

Abstract: Intracranial volume compensatory changes explained by the MonroKellie hypothesis (MKH) occur in spontaneous intracranial hypotension (SIH) and may be seen on MR imaging. 1 This case illustrates previously unreported findings on postcontrast fluid-attenuated inversion recovery (FLAIR) imaging conforming to the MKH, including diffuse pachymeningeal enhancement and gadolinium diffusion into the subdural space. It also highlights an additional compensatory mechanism of subarachnoid seepage seen as gadolinium opaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 4 publications
3
17
0
Order By: Relevance
“…5,6 This finding is important because treatment with either directed blood patch, fibrin glue injections, or surgery requires preprocedural knowledge of the site of CSF leak. Although intrathecal administration remains an FDA off-label use of gadolinium, all patients in our study tolerated intrathecal gadolinium without complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 This finding is important because treatment with either directed blood patch, fibrin glue injections, or surgery requires preprocedural knowledge of the site of CSF leak. Although intrathecal administration remains an FDA off-label use of gadolinium, all patients in our study tolerated intrathecal gadolinium without complications.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 A reduction in CSF volume leads to compensatory dilation of venous structures in the brain, which may result in headache and subdural collections via meningeal traction. 5,6 Severe untreated cases of SIH can lead to coma and stroke. 7 CT myelography (CTM) has historically been considered the study of choice for the detection and localization of CSF leak, though a criterion standard test is difficult to establish, given the varied etiologies for SIH.…”
mentioning
confidence: 99%
“…When gadolinium(Gd)-based contrast medium are used, MR signal contrast between pre-contrast and post-contrast MR images can often be observed in the CSF at certain locations within the intra-cranial space. [11][12][13][14] This is mainly due to the fact that the dural blood vessels lack a blood-brain barrier (BBB) that presents in cortical blood vessels, which enables some of the commonly used Gd contrast agents in human clinical MRI scans to cross the dural blood vessel wall and to enter the CSF. Recent studies have shown that some meningeal lymphatic vessels in the brain can be visualized using MRI with Gd contrast in human brains.…”
Section: Introductionmentioning
confidence: 99%
“…injection, the Gd contrast leaks out from the dural blood vessels, which lacks a BBB into the CSF. [11][12][13][14] However, this is a very rough estimation, and Gd concentration is known to be a key factor that can have dramatic effects on MR signals. 34 Figure 2 shows simulation results for the relationship between the maximum contrast in the CSF with and without Gd and the concentration of Gd in CSF.…”
mentioning
confidence: 99%
“…Lumbar epidural blood patches are commonly applied in patients resistant to conservative therapy. Targeted epidural blood patch, fibrin glue injections and surgical dural repair are treatment options needing correct localization of CSF leakage [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%